KUALITAS PELAYANAN OBJEK WISATA SANG NILA UTAMA MUSEUM IN PEKANBARU - M. Alif Fahri Alrawi; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the quality of service obtained at the Sang Nila Utama tourist attraction and to know government efforts in improving the quality of service at the Sang Nila Utama Museum tourist attraction. This study uses a quantitative method with a descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. The key informants in this study were 1 person from the Head of the Sang Nila Utama Museum. In this study, data collection techniques used were questionnaire, interview, observation and documentation. Based on the results of the study, it can be concluded that the Quality of Service in the Main Nila Museum Tourism Object in Pekanbaru City is already good in almost all things, they are Reliability (Reliability), Ressponsivenes (Ressponsivenes), Assurance (Assurance) and than Empathy (Empathy) that refer to the grand theory used on this melakukan about Service Quality at Sang Nila Utama Museum in Pekanbaru City, but there are also some things that are still not good in the quality of service. Keywords: Service Quality, perception, visitors